Evaluation of Diffusional Kurtosis Imaging in Sub-acute Ischemic Stroke: Comparison with Rehabilitation Treatment Effect. Issue 8 (August 2019) - Li, C.; Lan, C.; Zhang, X.; Yin, L.; Hao, X.; Tian, J.; Lin, L.; Sun, H.; Yao, Z.; Feng, X.; Jia, J.; Yang, Y.
Stroke is a serious worldwide medical condition that causes neurological function disability. Diffusional kurtosis imaging, which measures the non-Gaussianity of water diffusion, has been demonstrated to be a sensitive biomarker in many neuro-pathologies. This study explores the relationship between neural function recovery and transformation of the ischemic lesion and/or corticospinal tract during the sub-acute phase after stroke by using diffusional kurtosis imaging. We performed a prospective study of function recovery and K metrics of 43 patients with sub-acute ischemic stroke in the middle cerebral artery territory. The effect of rehabilitation treatment was evaluated using both the Fugl-Meyer motor function score and modified Barthel index score at post-treatment compared with admission, and patients were allocated to two groups: good and poor rehabilitation effect (GRE and PRE). Metrics of diffusional kurtosis imaging within ischemic lesion and along the corticospinal tract were acquired, respectively. All three relative axial diffusional kurtoses (rKas) along the corticospinal tract in the GRE group ( n = 21) were significantly larger than those of the PRE group ( n = 22), including rKa in the posterior limb of internal capsule, rKa in the cerebral peduncle, and rKa in the basal part of the pons ( p = 0.014, 0.005, and 0.021, respectively). This multi-parametric magnetic resonance imaging study showed that diffusional kurtosis imaging has the potential to complement existing stroke imaging techniques and revealed its own advantages in elucidating the possible biophysical mechanism of functional restoration underlying ischemic stroke.